Thermodynamics of surfaces and interfaces : concepts in inorganic materials - Meier, Gerald H., 1942- (Cambridge University Press, 2014)
"An accessible yet rigorous discussion of the thermodynamics of surfaces and interfaces, bridging the gap between textbooks and advanced literature by delivering a comprehensive guide without an overwhelming amount of mathematics. The book begins with a review of the relevant aspects of the thermodynamics of bulk systems, followed by a description of the thermodynamic variables for surfaces and interfaces. Important surface phenomena are detailed, including wetting, crystalline systems (including grain boundaries), interfaces between different phases, curved interfaces (capillarity), adsorption phenomena and adhesion of surface layers. The later chapters also feature case studies to illustrate real-world applications. Each chapter includes a set of study problems to reinforce the reader's understanding of important concepts. Ideal as an auxiliary text for students and a self-study guide for industry practitioners and academic researchers working across a broad range of materials"--Provided by publisher